The Interpretation of Racism in the Film "Green Book" from Roland Barthes' Semiotics Perspective - Priyagung Wicaksonno (DIGICOM : Jurnal Komunikasi dan Media, 2023)
Racism in the United States continues to be an enduring issue from generation to generation. Various forms of racial discrimination have remained ingrained in the social life of American citizens. The formation of stereotypes, negative prejudices, and the division of society based on skin color, between white and black individuals, have been triggering factors for the emergence of racism. White Americans still hold a position of high supremacy over black Americans. Film is a mass audio-visual medium believed to have the potential to influence its audience and depict or reconstruct realities of a phenomenon or issue, which is then presented in the form of a movie. The film "Green Book" is an adaptation of a true story that took place in the 1960s, a time when racism against black individuals by white individuals was prevalent. The purpose of this research is to describe the representation of racism in the film "Green Book." The method used in this research is Roland Barthes' semiotics, which focuses on the discovery of signifiers and signifieds in the object of study, namely the film "Green Book." It is formulated into three levels: denotative meaning, connotative meaning and myths, as well as the theory of racism. The results of this research show that the film "Green Book" depicts various instances of racism against black individuals in the United States. The portrayal of racism includes insults, marginalization, discrimination in physical and social status.